Concordance between computerised gait analysis and physical examination in patients with augmented femoral anteversion (2018)
Introduction: Human gait is the highest point in a person's functional independence; therefore, its importance as a movement pattern has led to the development of measuring tools. Objective: To assess the concordance between 2 measuring tools: computerised gait analysis (CGA) and physical examination (PE) in patients with increased femoral anteversion without neurological alterations. Methods: We conducted an observational analytic study of concordance. Data were obtained retrospectively from 2010 to 2014 in the gait analysis laboratory of the Roosevelt Children's Orthopaedics Institute through a single application of CGA and PE. Results: There were evident alterations in the PE because, at the hip, the internal-external rotation range decreases in the stance and swing phases. In the knee, there was a decrease in the flexion-extension range during the swing phase and in the ankle there was also a decrease in the dorsiflexion-plantarflexion range in the stance and swing phases. Conclusion: This study found that there was no concordance between PE and CGA. Therefore, these tests are complementary and provide information for a differential approach in clinical decision-making. © 2017 Elsevier España, S.L.U. y SERMEF